An organic copolymer for removing radioactive cesium from water

By preparing a new type of carbon nitride organic copolymer, the problem of low efficiency and slow speed of existing ion exchange materials when removing radioactive cesium in water is solved, and efficient and economical Cs ion removal effect is achieved, and good renewability is achieved.

CN116281894BActive Publication Date: 2025-03-11GUANGZHOU UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310222861.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-03-11
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

When removing radioactive cesium (Cs) from water, existing ion exchange materials have problems such as slow adsorption speed, low efficiency, poor selectivity and high cost.

Method used

The material is prepared by a new carbon nitride organic copolymer through specific synthesis steps, including the use of raw materials such as melamine, melamine and isopropanol. After multiple stirring, filtration, drying, calcining and grinding, etc., the efficient organic copolymer ion exchange material is finally obtained.

Benefits of technology

This material can quickly and efficiently remove Cs ions in water, has the advantages of high adsorption efficiency, good selectivity, low cost and easy regeneration, and has a small impact on other ions and pH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116281894B_ABST
    Figure CN116281894B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ion exchange water treatment, and in particular to an organic copolymer for removing radioactive cesium in water. The preparation method of the organic copolymer comprises the following steps: a. mixing melamine, cyanuric acid and isopropanol to obtain a white suspension; b. vacuum filtering the white suspension to filter liquid, washing, drying, grinding the remaining white solid to be uniform, placing it in a crucible, and placing it in a tube furnace for heating and calcining to obtain a yellow solid; c. weighing the yellow solid, placing it in a mortar, adding deionized water and sodium thiocyanate to grind together, drying, grinding again to be uniform, placing it in a crucible, and placing it in a tube furnace for heating and calcining to obtain a light yellow solid; d. weighing a small amount of the light yellow solid after washing, drying and grinding, and mixing and stirring with a hydrochloric acid solution; e. vacuum filtering the obtained mixed solution to filter the hydrochloric acid, washing and drying the remaining solid, and grinding to obtain a light yellow powder as the final product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion exchange water treatment, and in particular relates to an organic copolymer used for removing radioactive cesium in water. Background Art

[0002] The rapid development of the nuclear industry has met the growing energy demand, but the disposal of the nuclear waste it produces has become an important factor restricting its widespread application. 137 Cs as 235 One of the fission products of U, it is one of the main radioactive sources of spent fuel (1230g / t). Its half-life can reach 30.17 years, and it can emit gamma rays, which have high solubility, strong migration ability and biological toxicity. If it enters the human body, it can cause cell damage, cancer and even death. 137 Once Cs is released into the environment, it will cause serious pollution to the surrounding environment and endanger the entire ecosystem. The solution to this problem is undoubtedly to 137 Cs is separated from nuclear waste. The existing technologies include extraction, coprecipitation, adsorption, reverse osmosis and ion exchange. Among them, ion exchange has attracted widespread attention due to its simple operation, low cost and high efficiency. The existing ion exchange materials include natural minerals and artificial materials. Natural minerals include clay, mica and montmorillonite, and artificial materials include zeolite, titanate, layered hydroxide, potassium ferrocyanide, etc. There are many defects in the application of the above materials in ion adsorption, including slow adsorption rate, low adsorption efficiency and poor selectivity. Based on these aspects, it is imperative to prepare a new material with high efficiency, low price and simple synthesis. Carbon nitride organic copolymers have attracted the attention of researchers in various fields due to their simple synthesis method, wide source of precursors, high stability, low price and non-toxicity. Although carbon nitride organic copolymers have so many advantages, their application in the field of ion exchange has rarely been reported. Now we have synthesized a new type of carbon nitride organic copolymer and applied it to the field of ion exchange, which shows great advantages compared with other ion exchange materials. Summary of the invention

[0003] In view of the above-mentioned defects of the prior art, the present invention is to address the shortcomings of existing ion exchange materials and propose a carbon nitride organic copolymer with excellent properties such as high adsorption efficiency, fast adsorption speed, low price, simple preparation, renewability and recyclability.

[0004] The purpose of the present invention is achieved by the following technical solutions:

[0005] The present invention provides a method for preparing an organic copolymer for removing radioactive cesium in water, comprising the following steps:

[0006] (1) Mixing melamine, cyanuric acid, deionized water and isopropanol in a certain proportion and stirring them uniformly to obtain a white suspension A;

[0007] (2) filtering the white suspension A using a vacuum filtration device, washing the remaining white solid with deionized water, and drying to obtain a white solid B;

[0008] (3) Grinding the white solid B into powder and placing it in a covered crucible, placing the crucible containing the powder in a tubular furnace with nitrogen flow for heating and calcining, and naturally cooling to room temperature to obtain a yellow solid C;

[0009] (4) Weigh a small amount of yellow solid C into a mortar, add deionized water and grind it evenly, then add a small amount of sodium thiocyanate, grind it evenly, and then vacuum dry it to obtain a yellow solid D;

[0010] (5) Grind the yellow solid D evenly and place it in a covered crucible, transfer the crucible to a tubular furnace with nitrogen flow for heating and calcining, and cool it naturally to room temperature to obtain a light yellow solid E;

[0011] (6) The light yellow solid E was washed with deionized water and then dried to obtain a light yellow solid F;

[0012] (7) After the light yellow solid F is ground evenly, a small amount of powdered light yellow solid F is weighed and placed in a beaker, and then an appropriate amount of hydrochloric acid solution is poured into the beaker, and the mixture is magnetically stirred at room temperature to obtain a suspension G;

[0013] (8) The suspension G is filtered to remove hydrochloric acid using a vacuum filtration device, and the remaining solid is washed with deionized water, dried, and ground evenly to obtain a light yellow powder H, which is the finished organic copolymer (CN-H).

[0014] Preferably, in step (1), melamine (≥99%) and cyanuric acid (≥98%) are analytically pure, with a mass ratio of 10g:10g; isopropanol (≥99.8%) is chromatographically pure, with an addition amount of 10uL; the amount of deionized water added is 100mL; the stirring device is a polytetrafluoroethylene rotor and a magnetic stirrer, the stirring speed is 500-700r / min, the stirring temperature is 20°C-35°C, and the stirring time is 24h.

[0015] Preferably, in step (2), the drying equipment is a blast drying oven, the drying temperature is 60° C., and the drying time is not less than 18 hours.

[0016] Preferably, in step (3), the nitrogen is high-purity nitrogen (≥99%), the gas flow rate is 150-400 mL / min, and the calcination temperature is 500° C.-650° C.

[0017] Further preferably, the nitrogen gas flow rate is 200 mL / min, the heating rate is 6.1° C. / min, the calcination temperature is 580° C., and the heating time is 4 h.

[0018] Preferably, in step (4), the mass ratio of the yellow solid C to sodium thiocyanate is 10 g:10 g, the amount of deionized water added is 5 mL, the drying temperature is 60° C., the NaSCN (≥98%) is analytical grade, and the vacuum drying time is not less than 18 h.

[0019] Preferably, in step (5), the nitrogen is high-purity nitrogen (≥99%), the gas flow rate is 150-400 mL / min, and the calcination temperature is 350° C.-450° C.

[0020] Further preferably, the nitrogen gas flow rate is 200 mL / min, the heating rate is 9° C. / min, the calcination temperature is 390° C., and the heating time is 3 h.

[0021] Preferably, in the step (6), during the washing process of the light yellow solid, deionized water is first added and stirred for 30 minutes, and then the liquid is removed by vacuum filtration, and the liquid is washed by repeating the above steps five times; during the drying operation, the drying temperature is 60°C.

[0022] Preferably, in step (7), the amount of powdery light yellow solid F is weighed to be 1 g; the concentration of hydrochloric acid is 1 mM, the added volume is 80 mL-120 mL; and the stirring time is 12 h.

[0023] More preferably, the volume of hydrochloric acid added is 100 mL.

[0024] Preferably, in the deionized water washing process in step (8), deionized water needs to be added and stirred for 30 minutes, and then the liquid is removed by vacuum filtration, and the liquid is washed three times by repeating the above steps; the drying equipment is an ordinary blast drying oven, the drying temperature is 60°C, and the drying time is not less than 12 hours.

[0025] In addition, the present invention also provides an organic copolymer prepared by the method.

[0026] The beneficial effects of the present invention are:

[0027] (1) The organic copolymer ion exchange material of the present invention can quickly remove Cs ions in wastewater with high removal efficiency.

[0028] (2) The ion exchange material of the present invention still has a high removal capacity for Cs ions under the influence of other ions and pH.

[0029] (3) The fixed bed flow test conducted by the ion exchange material of the present invention can maintain high efficiency in removing Cs ions for a long time.

[0030] (4) The ion exchange material of the present invention is regenerable and can be backwashed with a small amount of high-concentration sodium chloride solution to elute the enriched Cs ions.

[0031] (5) The organic copolymer ion exchange material of the present invention is a solid powder, which is easy to separate from water and can avoid causing "secondary pollution" to the water.

[0032] (6) The preparation method of the organic copolymer ion exchange material of the present invention is simple, the raw material source is wide and low-priced, and the finished product material is non-toxic and harmless. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0034] Figure 1 is the X-ray powder diffraction pattern (XRD) of the organic copolymer prepared in Examples 1, 2 and 3;

[0035] Figure 2 The X-ray powder diffraction pattern (XRD) of the organic copolymer prepared in Example 3 in the sodium chloride solution of various concentrations;

[0036] Figure 3 is a curve diagram of Cs adsorption by the organic copolymer prepared in Example 2;

[0037] Figure 4 This is a model diagram of the Cs isotherm adsorption curve of the organic copolymer prepared in Example 2;

[0038] Figure 5 The Cs adsorption curve of the organic copolymer prepared in Example 2 under different pH environments;

[0039] Figure 6 This is a Cs adsorption curve of the organic copolymer prepared in Example 2 under the interference of 0.5 mM other metal ions;

[0040] Figure 7 This is a graph showing the evaluation of Cs adsorption by the organic copolymer prepared in Example 2 in a fixed bed flow reactor;

[0041] Figure 8 This is a diagram showing the evaluation of Cs adsorption in a fixed bed flow reactor after saturated regeneration of the organic copolymer prepared in Example 2; DETAILED DESCRIPTION

[0042] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0043] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0044] The present invention is further described in conjunction with the following examples.

[0045] Example 1

[0046] A method for preparing a semi-finished organic copolymer for removing radioactive cesium from water comprises the following steps:

[0047] (1) Weigh 10 g of melamine and 10 g of cyanuric acid respectively into a 200 mL beaker, add 200 mL of deionized water and 10 uL of isopropanol, and place the beaker on a magnetic stirrer and stir at room temperature for 24 h to obtain a white suspension A;

[0048] (2) filtering the white suspension A obtained in step (1) using a vacuum filtration device, washing the remaining white solid with deionized water three times, and drying it in an oven at 60° C. to obtain a white solid B;

[0049] (3) Grinding the dried white solid B in step (2) into powder and placing it in a covered crucible, placing the crucible containing the powder in a tubular furnace with nitrogen flow and heating it to 580 degrees Celsius at a heating rate of 6.1°C / min for 4 hours, and naturally cooling it to room temperature to obtain a yellow solid C;

[0050] (4) Weigh 1 g of the yellow solid C obtained in step (3) and place it in a mortar. Add 5 mL of deionized water and grind it evenly. Then weigh 1 g of sodium thiocyanate and add it to the mortar. Grind it evenly and place it in a vacuum drying oven at 60° C. to dry it to obtain a yellow solid D.

[0051] (5) Grind the yellow solid D dried in step (4) evenly and place it in a crucible with a lid, transfer the crucible to a tubular furnace with nitrogen flow, heat the temperature to 390° C. at a heating rate of 9° C. / min, heat for 3 h, and cool naturally to room temperature to obtain a light yellow solid E;

[0052] (6) The light yellow solid E in step (5) was washed five times with deionized water and dried in an oven at 60° C. to obtain a light yellow solid F, which is a semi-finished product of an organic copolymer (CN-Na);

[0053] Example 2

[0054] A method for preparing an organic copolymer for removing radioactive cesium from water comprises the following steps:

[0055] (1) The semi-finished organic copolymer (CN-Na) dried in Example 1 was ground evenly, 1 g was weighed and placed in a 200 mL beaker, and then 100 mL of 1 mM hydrochloric acid was poured into it. The beaker was placed on a magnetic stirrer and stirred at room temperature for 12 h to obtain a suspension G;

[0056] (2) The suspension G in step (1) is filtered of hydrochloric acid using a vacuum filtration device, and the remaining solid is washed three times with deionized water and dried in an oven at 60° C. The dried solid is evenly ground to obtain a light yellow powder H, which is the finished organic copolymer (CN-H).

[0057] Example 3

[0058] (1) Weigh 0.5 g of the finished organic copolymer (CN-H) in Example 2 and put it into a 200 mL beaker, then pour 100 mL of 0.5 mM cesium chloride solution into the beaker, and place the beaker on a magnetic stirrer and stir for 2 h to allow the organic copolymer (CN-H) to fully adsorb Cs ions, thereby obtaining a mixed solution A.

[0059] (2) The mixed solution A in step (1) is filtered using a vacuum filtration device, and the remaining solid is washed three times with deionized water, placed in an oven at 60° C. for drying, and the dried solid is evenly ground to obtain a light yellow powder B, which is the organic copolymer (CN-Cs) that has completely adsorbed Cs ions.

[0060] Test Examples (Characterization of Examples 1, 2, and 3)

[0061] Figure 1 Shown are the XRD spectra of the carbon nitride organic copolymers prepared in Examples 1, 2, and 3. The peak at 27.6° in the figure is the (002) crystal plane of the carbon nitride organic copolymer, representing the layered stacking structure of the carbon nitride organic copolymer. The peak of the (002) crystal plane represented by CN-Na and CN-H has not changed much and the spectra of the two are basically consistent, indicating that the layered stacking structure of the carbon nitride organic copolymer has not changed after being soaked in hydrochloric acid, and the overall crystal shape has not changed much. By comparing the spectra of CN-Cs and the other two materials, it can be seen that the peak of the (002) crystal plane represented by CN-Cs has become very weak. This is because the Cs ions replace the Na ions, resulting in the distortion of the structure of the carbon nitride organic copolymer. Surprisingly, this structural distortion can be restored to its original structure by means of ion exchange. Figure 2As shown in the figure, CN-Cs is immersed in sodium chloride solutions of different concentrations, so that Na ions can replace Cs ions again, and the peak representing the (002) crystal plane gradually increases, which indicates that the structure is gradually recovering. About 2wt.% of sodium chloride solution is enough for the structure of CN-Cs to recover to the appearance of CN-H. Then increasing the concentration of sodium chloride will not further increase the peak of the (002) crystal plane, because the space that can accommodate Na ions is saturated and cannot further adsorb Na ions.

[0062] Test Example 2 (Application Experiment)

[0063] Experimental process 1: Weigh 20 mg of the copolymer CN-H prepared in Example 2 into a 50 mL beaker, add 40 mL of deionized water, and stir evenly on a magnetic stirrer after ultrasonic treatment for 10 minutes. Then add 0.5 mM CsCl solution to the solution to start adsorption. The reaction is carried out at room temperature. Samples are taken at different time points, and then a 0.2 um polytetrafluoroethylene filter is used to intercept the material. The filtered liquid is used as a sample to measure the residual amount of Cs ions using ICP-OES.

[0064] Experimental process 2: Weigh 20 mg of the copolymer CN-H prepared in Example 2 into a 50 mL beaker, add 40 mL of deionized water, and stir evenly on a magnetic stirrer after ultrasonic treatment for 10 minutes. Then, add CsCl solutions of different concentrations into the solution to start adsorption. The reaction is carried out at room temperature for 30 minutes, and then the material is intercepted by a 0.2 um polytetrafluoroethylene filter. The remaining liquid is used as a sample to measure the remaining amount of Cs ions using ICP-OES.

[0065] Experimental process 3: Weigh 20 mg of the organic copolymer CN-H prepared in Example 2 into a 50 mL beaker, add 40 mL of deionized water, and stir evenly on a magnetic stirrer after ultrasonic treatment for 10 min. Then adjust the pH using hydrochloric acid and sodium hydroxide solution. After the pH is adjusted, add 0.5 mM CsCl solution to the solution to start adsorption. The reaction is carried out at room temperature. Samples are taken at different time points, and then a 0.2 um polytetrafluoroethylene filter is used to intercept the material. The remaining liquid is used as a sample to measure the remaining amount of Cs ions using ICP-OES.

[0066] Experimental process 4: Weigh 20 mg of the organic copolymer CN-H prepared in Example 2 into a 50 mL beaker, add 40 mL of deionized water, and stir evenly on a magnetic stirrer after ultrasonication for 10 min. Then add 0.5 mM CsCl solution and 0.5 mM other metal ions (Na + , K + , Ca 2+ Mg 2+ , Sr2+ ) solution begins to adsorb, the reaction is carried out at room temperature, samples are taken at different time points, and then the material is retained by a 0.2um polytetrafluoroethylene filter. The remaining liquid is used as a sample to measure the remaining amount of Cs ions using ICP-OES.

[0067] Experimental process 5: Weigh 1g of the organic copolymer CN-H prepared in Example 2 and mix it with 5g of quartz sand, put it into the flow column, and then weigh 25g of quartz sand to seal the two ends of the flow column. The two ends of the flow column are connected to two hoses, and the flow direction is bottom-in and top-out, and the flow rate is 0.45mL / min. After starting the reaction, just take samples on time. When regenerating the material, just rinse it with 200mL of 10wt.% sodium chloride solution and then rinse it with deionized water.

[0068] Figure 3 This is the adsorption curve of the organic copolymer CN-H prepared in Example 2 for Cs ions.

[0069] like Figure 3 As shown, in the beaker experiment, CN-H can quickly remove Cs ions in water within 5 minutes, and the removal rate of Cs ions can reach 80%.

[0070] Figure 4 : isothermal adsorption curve model of Cs ion by the organic copolymer CN-H prepared in Example 2. As shown in the figure, in order to evaluate the adsorption capacity of CN-H for Cs ion, the isothermal adsorption curve model of Cs ion at different concentrations was studied. We used the Langmuir model, Freundlich model and Langmuir-Freundlich model to fit it. The R of the three models is 2 The correlation coefficients are 0.974, 0.932, and 0.993, respectively. The R 2 The correlation coefficient is the highest, which can better fit the isothermal adsorption curve of CN-H for Cs ions. It is worth noting that the adsorption capacity of CN-H for Cs ions can reach 248.20 mg g -1 , which is higher than many ion exchange materials currently available for Cs removal.

[0071] Figure 5 and Figure 6 The adsorption curve of the organic copolymer CN-H prepared in Example 2 for Cs ions in different water environments. Figure 5 As shown, the pH of the organic copolymer CN-H dispersed in water is 9.8. When the pH is adjusted, the adsorption performance of CN-H on Cs will decrease. It can be seen that the adsorption performance of CN-H in its natural state is the best and no additional changes are required. Figure 5It can be seen that adding the same molar number of other metal ions to the Cs ion solution will affect the adsorption of Cs ions. + , K + and Sr 2+ The three ions have little effect on the adsorption of Cs ions, while Mg 2+ and Ca 2+ The two ions interfere greatly with the adsorption of Cs ions. In practical applications, other processes are also required to first reduce the content of other interfering ions and then enrich and recover Cs ions.

[0072] Figure 7 and Figure 8 The following is a graph showing the adsorption evaluation of Cs by the unused organic copolymer CN-H and the regenerated organic copolymer CN-H prepared in Example 2 in a fixed bed flow reactor. Figure 7 As shown in the figure, the adsorption rate of CN-H on Cs ions in a fluidized fixed bed reactor can reach more than 98%, and it can maintain high efficiency and continuous operation for 102 hours. Figure 8 CN-H was regenerated by 10wt.% NaCl solution. The adsorption rate of Cs ions by the regenerated CN-H remained above 98%, and the total time of continuous high-efficiency adsorption was almost the same as that of the new material. This shows that CN-H can be fully regenerated with little loss, which is very beneficial for practical applications.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an organic copolymer for removing radioactive cesium from water, characterized in that: The following steps are involved: (1) Mix melamine, cyanuric acid, deionized water and isopropyl alcohol in a certain proportion and stir to obtain a white suspension A; (2) filtering the white suspension A using a vacuum filtration device, washing the remaining white solid with deionized water, and drying to obtain a white solid B; (3) Grinding the white solid B into powder and placing it in a covered crucible, placing the crucible containing the powder in a tubular furnace with nitrogen flow for heating and calcining, and naturally cooling to room temperature to obtain a yellow solid C; (4) Weigh a small amount of yellow solid C into a mortar, add deionized water and grind it evenly, then add a small amount of sodium thiocyanate, grind it evenly, and then vacuum dry it to obtain a yellow solid D; (5) Grind the yellow solid D evenly and place it in a covered crucible, transfer the crucible to a tubular furnace with nitrogen flow for heating and calcination, and cool it naturally to room temperature to obtain a light yellow solid E; (6) The light yellow solid E is washed with deionized water and then dried to obtain a light yellow solid F, which is a semi-finished product of the organic copolymer; (7) After the light yellow solid F is ground evenly, a small amount of powdered light yellow solid F is weighed and placed in a beaker, and then an appropriate amount of hydrochloric acid solution is poured into the beaker, and the mixture is magnetically stirred at room temperature to obtain a suspension G; (8) Filtering the hydrochloric acid from the suspension G using a vacuum filtration device, washing the remaining solid with deionized water, drying, and grinding it to obtain a light yellow powder H, which is the finished product of the organic copolymer; In the step (1), melamine and cyanuric acid are analytically pure, with a mass ratio of 10g:10g; isopropanol is chromatographically pure, with an addition amount of 10µL; the amount of deionized water added is 100mL; the stirring device is a polytetrafluoroethylene rotor and a magnetic stirrer, the stirring speed is 500-700r / min, the stirring temperature is 20°C-35°C, and the stirring time is 24h; In the step (3), the nitrogen is high purity nitrogen, the gas flow rate is 150-400 mL / min, and the calcination temperature is 500° C.-650° C.; In the step (4), the mass ratio of yellow solid C to sodium thiocyanate is 1 g:1 g, the amount of deionized water added is 5 mL, the drying temperature is 60° C., the sodium thiocyanate is analytical grade, and the vacuum drying time is not less than 18 h; In the step (5), the nitrogen is high-purity nitrogen, the gas flow rate is 150-400 mL / min, and the calcination temperature is 350° C.-450° C.; In the step (6), during the washing process of the light yellow solid, it is necessary to first add deionized water and stir for 30 minutes, then remove the liquid by vacuum filtration, and repeat step (6) for five times; during the drying operation, the drying temperature is 60°C; In the step (7), the amount of powdery light yellow solid F is weighed to be 1 g; the concentration of hydrochloric acid is 1 mmol / L, and the added volume is 80 mL-120 mL; In the deionized water washing process in step (8), it is necessary to first add deionized water and stir for 30 minutes, then use vacuum filtration to remove the liquid, and repeat step (8) three times; the drying equipment is an ordinary blast drying oven, the drying temperature is 60°C, and the drying time is not less than 12 hours.

2. The method for preparing an organic copolymer for removing radioactive cesium from water according to claim 1, characterized in that: In the step (2), the drying equipment is a blast drying oven, the drying temperature is 60° C., and the drying time is not less than 18 hours.

3. The method for preparing an organic copolymer for removing radioactive cesium in water according to claim 1, characterized in that: In the step (3), the gas flow rate is 200 mL / min, the calcination temperature is 580° C., the heating rate is 6.1° C. / min, and the heating time is 4 h.

4. The method for preparing an organic copolymer for removing radioactive cesium in water according to claim 1, characterized in that: In the step (5), the air flow rate is 200 mL / min, the calcination temperature is 390° C., the heating rate is 9° C. / min, and the heating time is 3 h.

5. The method for preparing an organic copolymer for removing radioactive cesium in water according to claim 1, characterized in that: In the step (7), the volume of hydrochloric acid solution added is 100 mL, and the stirring time is 12 h.

6. An organic copolymer for removing radioactive cesium from water, characterized in that: The method is prepared according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Inorganic luminescent material and preparation method thereof

    CN114806572A

  • Black-and-white silver halide photographic sensitive material and processing method therefor

    JP1996240876A